Producción y comercialización de viveros y su incidencia en el ingreso familiar del sector Primero de Mayo, cantón Quevedo, período 2007 – 2013 - Casanova Cevallos, Javier Patricio (2015)
This research was conducted in the canton Quevedo, for determining the production and marketing of nursery and its impact on household income sector of the first May. Quevedo Canton, period 2007 - 2013 Surveys were used to for the people living in the first sector canton May Quevedo, to meet the economic and social conditions that generates production and marketing of nursery After analyzing the information was reached the following conclusions 50% of the inhabitants of the May 1 industry engaged in the activity of production and marketing of nursery plants and have an average income of 500-1000 per month. In addition 44% said that their families 3 people working 83% of respondents expressed that the plant increased cost of production which are woodland and likewise 65% of them expressed that produce approximately over 1001 annually Nurseries plants sold more in the field of May 1 are the forest as Teak, Guayacan, raft, etc with 76%. Also 98% of people said they do not use any broadcast medium to market their products